The boundary between “Judaism” and “Aryanism”: Anti-Semitic logic, litigation, and bureaucratic practices relating to the classification of “half-Jews” in Occupied France (1940-1944) - Laurent Joly (L'Atelier du CRH)
Under the Occupation, the French Jewish Statute made no provisions for an intermediary status for individuals of mixed heritage (who the administration called “half-Jews”), to the contrary of Nazi legislation in Germany. Consequently, there were no first- or second-degree mixed-heritage people in France; one was either Jewish or not. But the criteria for defining whether or not “half-Jews” were of “the Jewish race” varied between German and French texts, case law, and the practices of specialized bureaucrats. The boundary between “Jewish” and “non-Jewish” was tenuous, often arbitrary, and shaped by religious affiliation, a divorce, a marriage, or other fact of life. Being classified on the “good” or “bad” side of the “barricade” (according to the formulation of George Montandon, the ethno-racial expert of the Paris Prefecture of Police and the Commissariat-General for Jewish Affairs [CGQJ]) was very often a matter of life or death. The administration (mainly the “Jewish Service” of the Prefecture of Police and the CGQJ) and the courts had to rule on thousands of “ambiguous cases.” The CGQJ delivered over 11,000 “Certificates of Non-Belonging to the Jewish Race” after painstaking investigations. This article considers the categories that agents of the State used to sort out these borderline cases, and tries to understand the root causes of this dogged quest to determine the legal and political boundary between “Jew” and “non-Jew.”